The endovascular management of a 3.5-cm gastroduodenal artery aneurysm presenting with gastritis and recurrent pancreatitis - Baraa Zuhaili (Thieme Medical and Scientific Publishers Pvt. Ltd., 2017)
Visceral artery aneurysms (VAAs) are a rare entity. Within this subset of aneurysms, gastroduodenal artery (GDA) aneurysms represent an even more rare occurrence. We present a case report of treating GDA aneurysm on semi-elective basis followed by literature review of the clinical presentation and mainstream treatment modalities. GO is a 65-year-old male, with 6-month history of recurrent epigastric pain. He was found to have acute pancreatitis and an adjacent 3.5-cm GDA aneurysm. After conservative treatment of pancreatitis, the aneurysm was treated with coil embolization of the sac and GDA. Most VAAs are asymptomatic; GDA aneurysms tend to present clinically with epigastric pain or pancreatitis. In addition, together with pancreaticoduodenal aneurysms, GDA aneurysms warrant immediate intervention once diagnosed. Open surgical options for VAAs include aneurysm resection with or without revascularization (i.e., bypass), aneurysm ligation, or end-organ resection (i.e., splenectomy). Endovascular repair involves coil embolization with or without stent placement. While endovascular modality continues to be the first choice for stable elective VAA patients, modality of treatment for ruptured VAA or unstable patients will vary according to the patient's overall status, operator's experience, and institute capacity.